2013
DOI: 10.1074/jbc.m112.401299
|View full text |Cite
|
Sign up to set email alerts
|

Cdk1 Protein-mediated Phosphorylation of Receptor-associated Protein 80 (RAP80) Serine 677 Modulates DNA Damage-induced G2/M Checkpoint and Cell Survival

Abstract: Background: RAP80, a component of the BRCA1-A complex, is crucial in the cell cycle checkpoint and DNA damage repair. Results: RAP80 phosphorylation by Cdk1 is important for sensitivity to ionizing radiation and G 2 /M checkpoint control. Conclusion: Cdk1-mediated RAP80 phosphorylation is important for the DNA damage response. Significance: The findings provide new implications for the interplay of the DNA damage signaling pathway and RAP80 phosphorylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…It has been reported that fenofibrate plays important role in anticancer properties via diverse mechanisms in recent years (Balfour et al, 1990;Pawlik et al, 2004;Saidi et al, 2006;Grabacka et al, 2006;Urbanska et al, 2008;Zak et al, 2010;Wilk et al, 2012;Cho et al, 2013;Zhao et al, 2013;Liang et al, 2013;Watanabe et al, 2013;Li et al, 2014). But the exact relationship between fenofibrate and irradiation has not explored.…”
Section: Jia Liu Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that fenofibrate plays important role in anticancer properties via diverse mechanisms in recent years (Balfour et al, 1990;Pawlik et al, 2004;Saidi et al, 2006;Grabacka et al, 2006;Urbanska et al, 2008;Zak et al, 2010;Wilk et al, 2012;Cho et al, 2013;Zhao et al, 2013;Liang et al, 2013;Watanabe et al, 2013;Li et al, 2014). But the exact relationship between fenofibrate and irradiation has not explored.…”
Section: Jia Liu Et Almentioning
confidence: 99%
“…Cells in the G2/M were most sensitive to irradiation and most resistant during the latter part of the S phase cell cycle (Cho et al, 2013) .Therefore, it is an effective strategy to increase the sensitivity of radiotherapy through inducing G2/M arrest (Hematulin et al, 2012;Cui et al, 2012). The cell cycle involves a series of events driven by cyclins and subsequent CDKs, which further activate transcription factor proteins for cell cycle progression from one phase to another.…”
Section: Jia Liu Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…The link between oxidative stress and bad outcomes in assisted reproduction techniques is based on numerous attacks that occur in cellular metabolism during the process of replication of genetic material and in the regulation of the cell cycle. These sites of regulation, which include G1/S, intra-S and G2/M are involved in the response to DNA damage [6]. Zhang et al [7] showed that Ƴ H2AX, a marker of DNA damage, appears in H-treated sperm 2 or 2 (like OS models) and also embryos fertilized with these sperms have delay for the cleavage, which implies an arrest at the control points of the cell cycle, specifically, G2/M through ATM → Chk1 → Cdc25B/Cdc25c signaling pathway [7].…”
Section: Discussionmentioning
confidence: 99%
“…Purification of GST-fusion protein The GST fusion protein was expressed in Escherichia coli and purified as previously described. 17 siRNA All siRNA duplexes used in this study were purchased from IDT(Integrated DNA Technologies, Inc). The sequence of NLBP siRNA1 and 2 are 5-AGAAATGAGAGATGAGCTA and AGAAGAGGTCAATGATAAA, respectively, and have been described previously.…”
Section: Plasmidsmentioning
confidence: 99%